Effect of hyperbaric air on endotoxin from Bacteroides fragilis strains - Chmelař, Dittmar; Kašíková, Adéla; Martineková, Petrana; Hájek, Michal; Rozložník, Miroslav; Brabec, Marek; Janečková, Jana; Vobejdová, Jana; Čižnár, Ivan (Folia microbiologica, 2018)
The aim of the project was to determine any effect of hyperbaric air on Bacteroides fragilis strains cultivated under hyperbaric conditions. Previously, it was hypothesized that there was a correlation between the presence of Bacteroides bacteria in patients preferring a meaty diet and cancer of the small intestine, and particularly of the large intestine and rectum. With respect to the fact that Bacteroides fragilis (BAFR) group are important producers of endotoxins, measurement and statistical evaluation of endotoxin production by individual strains of isolated Bacteroides species were used to compare bacteria isolated from various clinical samples from patients with colon and rectum cancer in comparison with strains isolated from other non-cancer diagnoses. Endotoxin production was proven by quantitative detection using the limulus amebocyte lysate (LAL) test in EU/mL. Production of endotoxins in these bacteria cultured under hyperbaric air conditions was higher than those strains cultured under normobaric anaerobic conditions. But these differences in endotoxin production were not statistically significant (t test with log-transformed data, p value = 0.0910). Based on a two-tier t test for lognormal data, it is possible to cautiously conclude that a statistically significant difference was found between endotoxin production by Bacteroides fragilis strains isolated from non-carcinoma diagnoses (strains (1-6) and strains isolated from colorectal carcinoma diagnoses (strains 7-8; Wilcoxon non-parametric test p = 0.0132; t test = 0.1110; t test with log-transformed data, p value = 0.0294).
Keywords: Endotoxins; Humans; Bacteroides fragilis; kyslík; Hyperbaric Oxygenation; lidé; hyperbarická oxygenace; Oxygen; endotoxiny; kolorektální nádory; Colorectal Neoplasms